Laparoscopic treatment of intestinal malrotation in neonates and infants: retrospective study - Hagendoorn, Jeroen (Springer-Verlag, 2010)
BACKGROUND: Intestinal malrotation in neonates or infants may require urgent surgical treatment, especially when volvulus and vascular compromise of the midgut are suspected. Successful laparoscopic management of malrotation has been described in a number of case reports. It remains unclear, however, whether laparoscopy for the treatment of malrotation has a success rate equal to that of open surgery and what relative risks exist in terms of conversion and redo surgery in larger numbers of patients. This report describes a retrospective analysis of the clinical outcome for 45 children who underwent laparoscopic treatment of intestinal malrotation at the authors’ institution. METHODS: The 45 patients in this series, ages several days to 13 years, underwent a diagnostic laparoscopy for suspected intestinal malrotation. For 37 patients, malrotation with or without volvulus was diagnosed. All these patients underwent laparoscopic derotation and Ladd’s procedure. RESULTS: Successful laparoscopic treatment of intestinal malrotation could be performed in 75% of the cases (n = 28), and conversion to an open procedure was necessary in 25% of the cases (n = 9). The median hospital stay was 11 days (range, 2–60 days). Postoperative clinical relapse due to recurrence of malrotation, volvulus, or both occurred for 19% of the laparoscopically treated patients (n = 7). These patients underwent laparoscopic (n = 1) or open (n = 6) redo surgery. CONCLUSION: Diagnostic laparoscopy is the procedure of choice when intestinal malrotation is suspected. If present, malrotation can be treated adequately with laparoscopic surgery in the majority of cases. Nevertheless, to prevent recurrence of malrotation or volvulus, a low threshold for conversion to an open procedure is mandated.